Intraosseous access: a simulation analysis - Antov Miki; Bartolomeo Rinaldi; Bergesio Giorgio; Vallana Vittoria; Roasio Agostino (Infermieristica Journal)
Introduction: The priority in critical patients is to find a vascular access. The most used access is the peripheral venous access, but when its placement goes wrong or is difficult, the literature recommends implementing intraosseous (IO) access as a valid alternative. The IO access is a rapid, reliable and a relatively safe method. Despite the recommendations, IO access is rarely used when indicated. The objective of this study was to evaluate the critical points of the IO procedure, positioning time, percentage of success at first attempt in simulation and, in according to obtained outcomes, checking of the procedure inclusion within university programs.